How to qualify the vegetation in public squares to help the management of urban ecosystem services? - Bobrowski, Rogerio; Aguiar, Jéssica Thalheimer de; Cuchi, Tarik (Ciência e Natura, 2022)
We adopted procedures to analyze the floristic composition of public squares in Irati, Paraná, in order to diversify the provision of methods to generate information for public management. We found that describing the ratio of taxa may not be efficient for presenting problems regarding species diversification. Species diversity analysis should be divided into tree quantity and canopy area to determine the benefits that could be lost from removing exotic species. Using the procedure that considers crown area is more effective for estimating the cover value of the species. The diameter distribution, total height, and crown area curves can help management decisions about new plantings and prioritize risk assessment. The results of spatial indices can complement the information about data distribution.